4-Hydroxyisoleucine ameliorates an insulin resistant-like state in 3T3-L1 adipocytes by regulating TACE/TIMP3 expression - Gao F; Du W; Zafar MI; Shafqat RA; Jian L; Cai Q; Lu FR (Drug Design, Development and Therapy, 2015)
Feng Gao,1 Wen Du,1,4 Mohammad Ishraq Zafar,1 Raja Adeel Shafqat,2 Liumeng Jian,1 Qin Cai,1 Furong Lu3 1Department of Endocrinology, Union Hospital, 2Department of Medicine, Tongji Hospital, 3Department of Integrated Traditional Chinese and Western Medicine, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, 4Chengdu First People’s Hospital, Sichuan, People’s Republic of China Background: Obesity-associated insulin resistance (IR) is highly correlated with soluble tumor necrosis factor-α (sTNF-α), which is released from transmembranous TNF-α by TNF-α converting enzyme (TACE). In vivo, TACE activity is suppressed by tissue inhibitor of metalloproteinase 3 (TIMP3). Agents that can interact with TACE/TIMP3 to improve obesity-related IR would be highly valuable. In the current study, we assessed whether (2S,3R,4S)-4-hydroxyisoleucine (4-HIL) could modulate TACE/TIMP3 and ameliorate an obesity-induced IR-like state in 3T3-L1 adipocytes. Materials and methods: 3T3-L1 adipocytes were incubated in the presence of 25 mM glucose and 0.6 nM insulin to induce an IR-like state, and were then treated with different concentrations of 4-HIL or 10 µM pioglitazone (positive control). The glucose uptake rate was determined using the 2-deoxy-[3H]-d-glucose method, and the levels of sTNF-α in the cell supernatant were determined using ELISA. The protein expression of TACE, TIMP3, and insulin signaling-related molecules was measured using western blotting. Results: Exposure to high glucose and insulin for 18 hours increased the levels of sTNF-α in the cell supernatant. The phosphorylation of insulin receptor substrate-1 (IRS-1) Ser307 and Akt Ser473 was increased, whereas the protein expression of IRS-1, Akt, and glucose transporter-4 was decreased. The insulin-induced glucose uptake was reduced by 67% in 3T3-L1 adipocytes, which indicated the presence of an IR-like state. The above indexes, which demonstrated the successful induction of an IR-like state, were reversed by 4-HIL in a dose-dependent manner by downregulating and upregulating the protein expression of TACE and TIMP3 proteins, respectively. Conclusion: 4-HIL improved an obesity-associated IR-like state in 3T3-L1 adipocytes by targeting TACE/TIMP3 and the insulin signaling pathway. Keywords: 4-hydroxyisoleucine, obesity-related insulin resistance, soluble TNF-α, TACE, TIMP3, insulin signaling, glucose uptake, Fenugreek seed